Experimental study on the performance of multi-layered bulletproof vest - Azhari Sastranegara; Edmun Halawa; Lydia Anggraini (Universitas Mercu Buana, 2022)
A bulletproof vest should have high strength and durability to resist a bullet as vital war equipment. However, the cost of creating good quality bulletproof vest is expensive. Therefore, research about an alternative bulletproof vest with affordable cost and competitive quality is needed. This research aims to review and compare two alternative vest types with one commercial type IV vest. Both alternative vests have similar components, except the second one has an additional Ultra High Molecular Weight Polyethylene (UHMWPE) component. The ballistic test shows that alternative vests are still not enough to resist a 5.56 mm bullet, but it has the potency to handle a 9 mm bullet. Furthermore, the influence of UHMWPE to resist 9 mm bullets is shown in this research.